Stopping Onabotulinum Treatment after the First Two Cycles Might Not Be Justified: Results of a Real-life Monocentric Prospective Study in Chronic Migraine - Sarchielli, Paola; Romoli, Michele; Corbelli, Ilenia; Bernetti, Laura; Verzina, Angela; Brahimi, Elona; Eusebi, Paolo; Caproni, Stefano; Calabresi, Paolo (Frontiers in Neurology, 2017)
Introduction: Onabotulinum toxin A (OnabotA) cyclic treatment is approved for the prophylactic treatment of chronic migraine (CM), a highly disabling disorder. Although treatment response varies among patients, current guidelines suggest to stop treatment after cycle 2 if no response is achieved. This prospective study aimed to define, in real-life setting, the evolution of the response to OnabotA over 5 cycles of treatment among patients non-responders to cycle 1. The results of this study might help in decision making, in particular whether prosecuting OnabotA further or not, when facing a patient not responding to cycle 1. Methods: Patients failing to respond at cycle 1 were recruited to complete 5 cycles. Key outcomes were: (i) a ≥50% reduction in headache days, (ii) a ≥50% reduction in total cumulative hours of headache on headache days and (iii) a ≥5-point improvement in HIT-6 scores. Results: Overall, 56 patients were included. Mean age was 45.7 years (female 83.9%). Severe (≥60) HIT-6 score was reported at baseline by 95.8% of patients. Responders (headache days reduction of more than 50%) progressively increased cycle after cycle, doubling from cycle 2 to cycle 5 (from 27% to 48%). In addition, patients regressed from CM to episodic migraine (EM) moving on with each cycle, with 78% of them reaching less than 9 migraine days/month after cycle 5. The headache days per month decreased significantly from cycle 1 to cycle 5 (overall from 23.3 ± 5.7 to 9.2 ± 3.6; p<0.001). During 12 months (5 cycles), migraine days per month progressively abated (from 18.5 to 8.7; p<0.001), days with symptomatic medications intake/month consistently decreased (from 17.4 to 8.1; p<0.001), and mean HIT-6 score lowered (from 72.4 ± 5.7 to 50.2 ± 4.3; p<0.001). Conclusions: The positive effect of OnabotA treatment spreads over the course of the treatment, and might also manifest late in treatment course among patients with no benefit after the first 2 cycles. Thus, the results of this real-life study suggest to extend OnabotA treatment further, beyond cycle 2, to avoid premature withdrawal in patients who would have become responders at cycle 3, 4 or 5.